An Analysis of Code Mixing Found in the Indonesian Movie: Cek Toko Sebelah - Putu Rosalina Adnyani; Sang Ayu Isnu Maharani; Putu Weddha Savitri (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2023)
This study aims to 1) describe the types of code-mixing used by actors in the film "Cek Toko Sebelah" and 2) describe the reasons for using the code-mixing. This study uses a qualitative method. The object of this research is code-mixing contained in the film Cek Toko Next. This research data are in words, phrases, and sentences containing mixed codes of English and Indonesian. This study uses the observation method in collecting data. The data were then analyzed using Muysken's theory for the types of code-mixing. Based on the analysis conducted, this study found three code-mixing types: insertion code-mixing, alteration code-mixing, and congruent lexicalization code-mixing. In addition, there are two motives for using code-mixing used in the Indonesian film "Cek Toko Sebelah," namely the motive for filling in needs and the motif for filling in prestige.